The Thieves and acts of Banditry and their affects on Economic Activities in west Islamic Cities From (3-7/13-19) century - Obaid, Taha Kh.; Hasan, Idrees M. (Humanities Journal of University of Zakho, 2018)
Acts of thieves and acts of banditry are considered the dirtiest acts deprived by God. As mentioned in the Holy Quran “as for the man or woman who is guilty of theft, recompense them by cutting off their hands for their crimes. that is the punishment from Allah. Allah is mighty, wise. (38)”. These acts affected the economy and trade of the cities as well as stealing the commercial caravans and pilgrim’s caravans which affected Muslims’ interests in such area Because of such acts, importing and exporting of goods became more difficult to and from such areas. Moreover, taxes gained from trade were also affected by such acts. Since these theft acts affected the trade and economy of Islamic states in a bad way, Islamic states should have been ready to fight these thieves to secure commercial routes.The acts of thieves were more active during the weakness of the Abbasid state. Thieves usually make use of political circumstances to conduct their criminal acts. On the contrary, when the states are strong, they cannot conduct their criminal acts.